2009
DOI: 10.1016/j.biomaterials.2009.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cell proliferation and differentiation on an injectable calcium phosphate – Chitosan composite scaffold

Abstract: Calcium phosphate cement (CPC) can be molded or injected to form a scaffold in situ, has excellent osteoconductivity, and can be resorbed and replaced by new bone. However, its low strength limits CPC to non-stress-bearing repairs. Chitosan could be used to reinforce CPC, but mesenchymal stem cell (MSC) interactions with CPC-chitosan scaffold have not been examined. The objective of this study was to investigate MSC proliferation and osteogenic differentiation on high-strength CPC-chitosan scaffold. MSCs were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
156
0
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 213 publications
(163 citation statements)
references
References 55 publications
(66 reference statements)
2
156
0
3
Order By: Relevance
“…28 Some studies have reported that the aggregated space between the pores acts as the passageway for the metabolism of cells and the transportation of nutrition that promote the ingrowth of blood vessels. [29][30][31] Yoshikawa et al 32 suggested that the pore size in grafts used for bone healing should be at least 50 µm. Larger pore sizes result in greater quantities of nutrition and oxygen being transported into the inside of the scaffold.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Some studies have reported that the aggregated space between the pores acts as the passageway for the metabolism of cells and the transportation of nutrition that promote the ingrowth of blood vessels. [29][30][31] Yoshikawa et al 32 suggested that the pore size in grafts used for bone healing should be at least 50 µm. Larger pore sizes result in greater quantities of nutrition and oxygen being transported into the inside of the scaffold.…”
Section: Discussionmentioning
confidence: 99%
“…31,33,34 However, Grynpas et al 33 noted that oversized pores not only reduce mechanical strength but also influence cell function and new bone formation. High levels of interconnectivity between the pores enhance the porosity and enlarge the superficial area and consequently increase the numbers of endothelial cells and active osteoblasts.…”
mentioning
confidence: 99%
“…These coatings are described to induce an increased bone-to-implant contact and are regarded as osteoinductive [65]. In vitro, several studies have shown that a calcium phosphate coated implant surface promotes osteogenic differentiation of mesenchymal stem cells, which implies a stimulating effect of calcium phosphate for the formation of new bone [66][67][68].…”
Section: Cell Regulation By Chemical Characteristics Of a Materialsmentioning
confidence: 99%
“…The ALP activity of MG 63 cells cultured on the MCPB was significantly higher than that of CPB and the control (TCP) at 7 and 14 days ( p , 0.05). A previous study showed that the ALP for mesenchymal stem cells on CPC -chitosan was higher than on CPC at 14 days (Moreau & Xu 2009). There were no significant differences for ALP at 7 and 14 days for the same sample.…”
Section: Degradation In Tris -Hcl Solutionmentioning
confidence: 99%